2012
DOI: 10.1377/hlthaff.2011.1356
|View full text |Cite
|
Sign up to set email alerts
|

In Urban And Rural India, A Standardized Patient Study Showed Low Levels Of Provider Training And Huge Quality Gaps

Abstract: This article reports on the quality of care delivered by private and public providers of primary health care services in rural and urban India. To measure quality, the study used standardized patients recruited from the local community and trained to present consistent cases of illness to providers. We found low overall levels of medical training among health care providers; in rural Madhya Pradesh, for example, 67 percent of health care providers who were sampled reported no medical qualifications at all. Wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
313
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(323 citation statements)
references
References 27 publications
9
313
1
Order By: Relevance
“…Two recent studies that use mystery clients to assess the quality of care in an outpatient setting are Currie, Lin, and Zhang (2010) and Das et al (2012), although many other studies have used mystery clients to assess such topics as the availability of medicines in pharmacies. Madden et al (1997) report on the use of mystery clients in a variety of settings (and refer to the clients as "undercover care seekers" and "simulated clients").…”
Section: Instrumentsmentioning
confidence: 99%
“…Two recent studies that use mystery clients to assess the quality of care in an outpatient setting are Currie, Lin, and Zhang (2010) and Das et al (2012), although many other studies have used mystery clients to assess such topics as the availability of medicines in pharmacies. Madden et al (1997) report on the use of mystery clients in a variety of settings (and refer to the clients as "undercover care seekers" and "simulated clients").…”
Section: Instrumentsmentioning
confidence: 99%
“…These criteria were adapted from the literature on various approaches to assessing the quality of medical care. 13,15,16 In addition, we assessed the provider mix in each study, as studies that narrowly focus on one subset of providers (e.g., only allopathic doctors) may inadequately reflect the complexity of India's health system. Studies that had a participation/response rate of <50% or that included <20 providers were considered to be of very low quality and were excluded from the analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Results pertaining to the key standards, i.e., sputum examination for diagnosis (Standard 2), initiation of the recommended drug regimen among new TB cases (Standard 8), and patient support to ensure adherence (Standard 9), each with 10 or more studies, are presented here. The results pertaining to the remaining standards (1,5,10,13,18) are given in the Appendix.…”
Section: Data On Istc Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lack of clinical standards and guidelines and loose management over clinical practice can be another barrier for improving standard care, often resulting in unsafe care. Recent studies in India 18 and China 19,20 using simulated patients or clinical audit method helped reveal the low level of conformity to recommended care and severe shortcoming of providers in grassroots facilities to prescribe accurate diagnosis and treatment for the most basic health problems. Though evidence remains scare, a recent meta-analysis found that the prevalence of healthcareassociated infection were much higher in developing countries than in developed countries.…”
mentioning
confidence: 99%